Laporan Kasus : Gambaran Kongenital Kyphoscoliosis E.C. Hemivertebrae Thoracal 12 pada Anak 14 Tahun di Rumah Sakit Umum Daerah Dr Slamet Garut - Difa Ayu Zahranita H; Tika Mirantiayu; Amelia Kresna (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Introduction: The vertebral column supports the body and protects the spinal cord. Hemivertebra is a congenital anomaly caused by partial failure of vertebral body formation, with scoliosis as its most common complication. Hemivertebra-related scoliosis is progressive and may lead to spinal imbalance and severe deformity. Diagnosis can be established using prenatal ultrasonography, plain radiography, CT, and MRI. Plain radiography is typically used as an initial examination due to its accessibility, but it has limitations in complex deformities. CT scanning with three-dimensional reconstruction provides detailed vertebral visualization for preoperative planning, while MRI enables comprehensive evaluation of neural axis abnormalities without radiation exposure.Case Report: A 14-year-old boy presented to RSUD dr. Slamet Garut with complaints of an asymmetric appearance of the back, accompanied by a progressively enlarging lump on the back and right-sided lower back pain for the past three years. The patient also reported easy fatigability and excessive sweating during physical activity. Past medical history revealed pulmonary tuberculosis at the age of six months, for which the patient had completed treatment with no residual symptoms. Growth and developmental history indicated delays in motor and speech development. A contrast-enhanced thoracolumbar MSCT scan from vertebra Th1 to the sacrum performed revealed severe congenital kyphoscoliosis secondary to a fully segmented hemivertebra at Th12, with absence of the left pedicle and 12th rib, accompanied by suspicion of posterior spinal canal narrowing.Conclusion:  A 14-year-old boy was diagnosed with severe congenital kyphoscoliosis caused by a fully segmented hemivertebra at Th12, accompanied by abnormalities of the left pedicle and 12th rib, as well as suspected posterior spinal canal narrowing.